Tecnologia, uso, coleta e tratamento de dados: o futuro do poder econômico? - Duarte, Thaile Xavier Dantas (2020)
The revolutions in history have transformed the modes of production and consumption in society. But this was only possible due to the strong application of capital, which was most pronounced in the Industrial Revolution in the mid- 16th century. The broad expansion of the capitalist system accelerated the technological development that was marked by the increase of communication networks and the revolution in the computer sector. The concentration of economic power that has long been over material goods today is in immaterial goods, such as data or patented technologies. However, although it has brought many advances, the technological potential achieved by digital companies, brings with it some peculiar problems that never before existed, such as privacy and protection of personal data, or competition problems and concentration of digital economic power, just mentioning some. However, while information flows flow dynamically across networks, law has remained static for a long time, with a large gap remaining evident in the economic regulation of fully digital enterprises. Thus, it is urgent the action of the States in the control of the economic power of technology platforms in order to ensure the protection of society and the maximum use of technological advances. Therefore, the law must be adapted to reality, with the effective protection of personal data as a fundamental right. To this end, this paper will present the national and international context about the regulation of technology platforms, exposing some possible help tools in this complex journey.